Removal of Fluoroquinolones from Water Systems Employing Rice Husk Composited Sponges via Nanoadsorption - Kanaa, Dalia (AUC Knowledge Fountain, 2025)
A novel nanocomposite of polyvinyl alcohol formaldehyde (PVF) sponge loaded with green zinc oxide nanoparticles (ZnONP) and referred to as (NP-PVF) was fabricated as a potential adsorbent of ciprofloxacin from water. A simple mechanical foaming process was used to synthesize the adsorbent. Rice husk extract was used to synthesize zinc oxide nanoparticles (ZnONP) for its phytochemicals as reducing agents. A facile and low-energy-dependent extraction method was used that did not require the use of high-temperature annealing. The synthesized nanoparticles showed a maximum UV absorption at 347 nm, which corresponds to a 3.58 eV band gap energy. FTIR confirmed the successful synthesis of the nanoparticles and the composite, which showed the distinct band of metal-oxygen at [600-400] cm-1, which also appeared in the nanocomposite. XRD showed that the particles have a wurtzite structure, whereas the composite has an amorphous structure. The hydrodynamic particle size of the green zinc oxide was 758.33±16.8 nm, and the point of zero charge of ZnONP and NP-PVF was at +2.78 and +1.82, respectively. The nanosize of the particles was confirmed by TEM, which showed a mean size of 31.34nm. The elemental composition of ZnONP and NP-PVF was investigated using EDX. The nanocomposite showed super-hydrophilic performance due to its high content of hydroxyl groups. No enhancement in the thermal stability of NP-PVF was observed compared to the pristine PVF. The nanocomposite showed a reduction in the swelling degree compared to the PVF sponge to reach 461.92±19.41% and 94.23±0.4% after 1 hour for PVF and NP-PVF, respectively. The nanocomposite showed similar mechanical properties to the pristine PVF, recording a tensile strength of 37.83±6.52 KPa and a Young’s modulus of 34.03±5.21 KPa. The nanocomposite showed an irregular macroporous structure and a BET surface area of 0.87 m2/g. The total carbohydrate content was measured for the extract, ZnONP, and NP-PVF to be 43.2±0.094%, 14.3±0.093%, and 21.91±0.088%, respectively. In addition, the phenolic content was 39.64±0.121, 1.95±0.076, and 0.495±0.036 mg/g gallic acid equivalent, respectively. The antioxidant activities of the rice husk extract, green nanoparticles, and NP-PVF composite were also studied. NP-PVF was tested for its potential adsorption of ciprofloxacin. The optimal adsorption conditions were 10% nanoparticle load, 243 mg sponge dose, pH 6, initial concentration of 100 mg/L, and equilibrium time between 100 and 120 minutes. The maximum removal of ciprofloxacin obtained by applying these conditions was 81.17±0.17%. Ciprofloxacin adsorption using NP-PVF composite was best described by the Langmuir model and the pseudo-second-order model. In sum, the NP-PVF nanocomposite has the potential to remove ciprofloxacin from water efficiently. As PVF is rich with hydroxyl groups, it could be further modified to target different contaminants.